Characteristics and reproducibility of novel sleep EEG biomarkers and their variation with sleep apnea and insomnia in a large community-based cohort. Issue 10 (22nd June 2021) - Younes, Magdy; Azarbarzin, Ali; Reid, Michelle; Mazzotti, Diego R; Redline, Susan
Abstract: Study Objectives: New electroencephalogram (EEG) features became available for use in polysomnography and have shown promise in early studies. They include a continuous index of sleep depth (odds-ratio-product: ORP), agreement between right and left sleep depth (R/L coefficient), dynamics of sleep recovery following arousals (ORP-9), general EEG amplification (EEG Power), alpha intrusion and arousal intensity. This study was undertaken to establish ranges and reproducibility of these features in subjects with different demographics and clinical status. Methods: We utilized data from the two phases of the Sleep-Heart-Health-Study (SHHS1 and SHHS2). Polysomnograms of 5, 804 subjects from SHHS1 were scored to determine the above features. Feature values were segregated according to clinical status of obstructive sleep apnea (OSA), insomnia, insomnia plus OSA, no clinical sleep disorder, and demographics (age, gender, and race). Results from SHHS visit2 were compared with SHHS1 results. Results: All features varied widely among clinical groups and demographics. Relative to participants with no sleep disorder, wake ORP was higher in participants reporting insomnia symptoms and lower in those with OSA ( p < 0.0001 for both), reflecting opposite changes in sleep pressure, while NREM ORP was higher in both insomnia and OSA (p<0.0001), reflecting lighter sleep in both groups. There were significant associations with age, gender, and race. EEG Power, and REM ORP were highly reproducible across the two studies (ICC > 0.75). Conclusions: The reported results serve as bases for interpreting studies that utilize novel sleep EEG biomarkers and identify characteristic EEG changes that vary with age, gender and may help distinguish insomnia from OSA.